The appearance of a compact jet in the soft–intermediate state of 4U 1543−47. Issue 1 (1st May 2020) - Russell, D M; Casella, P; Kalemci, E; Vahdat Motlagh, A; Saikia, P; Pirbhoy, S F; Maitra, D
ABSTRACT: Recent advancements in the understanding of jet–disc coupling in black hole candidate X-ray binaries (BHXBs) have provided close links between radio jet emission and X-ray spectral and variability behaviour. In 'soft' X-ray states the jets are suppressed, but the current picture lacks an understanding of the X-ray features associated with the quenching or recovering of these jets. Here, we show that a brief, ∼4 d infrared (IR) brightening during a predominantly soft X-ray state of the BHXB 4U 1543−47 is contemporaneous with a strong X-ray type B quasi-periodic oscillation, a slight spectral hardening and an increase in the rms variability, indicating an excursion to the soft–intermediate state (SIMS). This IR 'flare' has a spectral index consistent with optically thin synchrotron emission and most likely originates from the steady, compact jet. This core jet emitting in the IR is usually only associated with the hard state, and its appearance during the SIMS places the 'jet line' between the SIMS and the soft state in the hardness–intensity diagram for this source. IR emission is produced in a small region of the jets close to where they are launched (∼0.1 light-seconds), and the time-scale of the IR flare in 4U 1543−47 is far too long to be caused by a single, discrete ejection. We also present a summary of the evolution of the jet and X-ray spectral/variability properties throughout the whole outburst, constraining the jet contribution to the X-ray flux during the decay.